Milk and honey - Kaur, Rupi (Andrews McMeel Publishing, 2018)
Milk and honey is a collection of poetry and prose about survival. About the experience of violence, abuse, love, loss, and femininity. The book is divided into four chapters, and each chapter serves a different purpose. Deals with a different pain. Heals a different heartache. Milk and honey takes readers through a journey of the most bitter moments in life and finds sweetness in them because there is sweetness everywhere if you are just willing to look.--Amazon.com.